Cardiac sympathetic denervation and synucleinopathy in Alzheimer's disease with brain Lewy body disease. Issue 1 (28th January 2020) - Serrano, Geidy E; Shprecher, David; Callan, Michael; Cutler, Brett; Glass, Michael; Zhang, Nan; Walker, Jessica; Intorcia, Anthony; Adler, Charles H; Shill, Holly A; Driver-Dunckley, Erika; Mehta, Shyamal H; et al.
Abstract: Comorbid Lewy body pathology is very common in Alzheimer's disease and may confound clinical trial design, yet there is no in vivo test to identify patients with this. Tissue (and/or radioligand imaging) studies have shown cardiac sympathetic denervation in Parkinson's disease and dementia with Lewy bodies, but this has not been explored in Alzheimer's subjects with Lewy bodies not meeting dementia with Lewy bodies clinicopathological criteria. To determine if Alzheimer's disease with Lewy bodies subjects show sympathetic cardiac denervation, we analysed epicardial and myocardial tissue from autopsy-confirmed cases using tyrosine hydroxylase and neurofilament immunostaining. Comparison of tyrosine hydroxylase fibre density in 19 subjects with Alzheimer's disease/dementia with Lewy bodies, 20 Alzheimer's disease with Lewy bodies, 12 Alzheimer's disease subjects without Lewy body disease, 19 Parkinson's disease, 30 incidental Lewy body disease and 22 cognitively normal without Alzheimer's disease or Lewy body disease indicated a significant group difference ( P  < 0.01; Kruskal–Wallis analysis of variance) and subsequent pair-wise Mann–Whitney U tests showed that Parkinson's disease ( P  < 0.05) and Alzheimer's disease/dementia with Lewy bodies ( P  < 0.01) subjects, but not Alzheimer's disease with Lewy bodies subjects, had significantly reduced tyrosine hydroxylase fibre density as compared with cognitively normal. Both Parkinson's disease and Alzheimer's disease/dementia with Lewy bodies subjects also showed significant epicardial losses of neurofilament protein-immunoreactive nerve fibre densities within the fibre bundles as compared with cognitively normal subjects ( P  < 0.01) and both groups showed high pathologic alpha-synuclein densities ( P  < 0.0001). Cardiac alpha-synuclein densities correlated significantly with brain alpha-synuclein ( P  < 0.001), while cardiac tyrosine hydroxylase and neurofilament immunoreactive nerve fibre densities were negatively correlated with the densities of both brain and cardiac alpha-synuclein, as well as Unified Parkinson's Disease Rating Scale scores ( P  < 0.05). The clear separation of Alzheimer's disease/dementia with Lewy bodies subjects from Alzheimer's disease and cognitively normal, based on cardiac tyrosine hydroxylase fibre density, is the first report of a statistically significant difference between these groups. Our data do not show significant sympathetic cardiac denervation in Alzheimer's disease with Lewy bodies, but strongly confirm that cardiac nuclear imaging with a noradrenergic radioligand is worthy of further study as a potential means to separate Alzheimer's disease from Alzheimer's disease/dementia with Lewy bodies during life. Abstract : In this study, we strengthen the rationale that sympathetic cardiac denervation might be driven by alpha-synuclein pathology, which suggests that an in vivo test for such denervation would allow clinical differentiation between subjects with Alzheimer's disease and subjects with dementia with Lewy bodies with comorbid Alzheimer's disease. Graphical Abstract: